Self-reported urinary impairment identifies ‘fast progressors’ in terms of neuronal loss in multiple system atrophy - Guevara, Carlos; de Grazia, José; Baabor, Pablo; Soruco, Wendy (Autonomic neuroscience, 2019)
MSA is an adult-onset, sporadic, progressive parkinsonian syndrome characterised by the presence of akinesia, cerebellar dysfunction, autonomic failure and pyramidal signs. Annualized-whole-brain atrophy rate (a-WBAR) is an informative way to quantify disease progression. In this longitudinal work we investigate the correlations of a-WBAR with clinical scales for motor impairment, autonomic disability and cognitive decline in MSA and explore how atrophy progresses within the brain. Fourty-one MSA patients were studied using Structural Imaging Evaluation with Normalization of Atrophy (SIENA). SIENA is an MRI-based algorithm that quantifies brain tissue volume. Clinical parameters were explored using the 18-item Movement Disorder Society-sponsored revision of the Unified Parkinson's Disease Rating Scale, the Hoehn and Yahr Scale, the Frontal Assessment Battery and the Natural History and Neuroprotection in Parkinson Plus Syndromes scale (sub-items for orthostatic and urinary functions). The mean (±SD) age was 60.4 years ± 7.7 and a-WBAR was 1.65% ± 0.9. Demographics and clinical ratings at the time of the first scan were non-significantly associated with a-WBAR. The only exception was the baseline urinary score with a weak but significant association (R2 = 0.15, p = 0.04). Progression of grey matter atrophy was detected in the left superior temporal gyrus, right middle frontal gyrus, right frontopolar region and midbrain. Urinary impairment at baseline may help to identify ‘fast progressors’ in terms of neuronal loss, particularly in the frontal and temporal lobes. Thus, urinary impairment should be recognized as a key target for disease modifying therapeutic interventions in MSA. •In MSA autonomic dysfunction within the first 3 years from the disease onset is associated with rapid progression to death.•In MSA urinary impairment at baseline may help to select ‘fast progressors’ in terms of neuronal loss.•Urinary impairment should be recognized as a key target for disease modifying therapeutic interventions in MSA.